2023
DOI: 10.1038/s41598-023-42749-z
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and geographical conditions influence color, physical properties, and physiochemical composition of pomegranate fruits

Ali Akbar Ghasemi-Soloklui,
Mojtaba Kordrostami,
Ali Gharaghani

Abstract: The highest quality pomegranate necessitates a tropical or subtropical environment for proper growth and development. This study evaluated two pomegranate cultivars including Rabab Poost Ghermez Neyriz (RPGN) and Makhmal Malas Shahreza (MMS) for physical traits, biochemical properties, and juice quality in their native locations as well as other warm and arid regions during two growing seasons (2019–2020 and 2020–2021) in Iran. The results showed that cultivars with the maximum redness (a*) were more likely to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The fruit weights of the cultivars 'Barski slatki', 'Konjski zub', 'Sladun', and 'Šerbetaš' were higher (and for 'Dividiš'-lower) than the fruit weights of the same cultivars grown in a production plantation under agroecological conditions in Metković, Croatia [24]. This was most likely due to different environmental conditions, as the study by Ghasemi-Soloklui [25] found that the change in the initial climate of pomegranate cultivars affects the weight of the fruit, aril, and peel. We divided the cultivars into three groups according to fruit weight: cultivars with medium ('Dubrovački kasni', 'Medunac', 'Mojdiški sitnozrni'), large ('Bokežan', 'Domaći kiseli', 'Glavaš', 'Kristal', 'Zamorac', 'Granada', and 'Wonderful'), and very large ('Barski slatki', 'Dividiš', 'Konjski zub', 'Pastun', 'Sladun', 'Slatki crveni', 'Slatki tankokorac', 'Šerbetaš', and 'Hicaznar') fruits.…”
Section: Morphological Characteristicsmentioning
confidence: 85%
“…The fruit weights of the cultivars 'Barski slatki', 'Konjski zub', 'Sladun', and 'Šerbetaš' were higher (and for 'Dividiš'-lower) than the fruit weights of the same cultivars grown in a production plantation under agroecological conditions in Metković, Croatia [24]. This was most likely due to different environmental conditions, as the study by Ghasemi-Soloklui [25] found that the change in the initial climate of pomegranate cultivars affects the weight of the fruit, aril, and peel. We divided the cultivars into three groups according to fruit weight: cultivars with medium ('Dubrovački kasni', 'Medunac', 'Mojdiški sitnozrni'), large ('Bokežan', 'Domaći kiseli', 'Glavaš', 'Kristal', 'Zamorac', 'Granada', and 'Wonderful'), and very large ('Barski slatki', 'Dividiš', 'Konjski zub', 'Pastun', 'Sladun', 'Slatki crveni', 'Slatki tankokorac', 'Šerbetaš', and 'Hicaznar') fruits.…”
Section: Morphological Characteristicsmentioning
confidence: 85%
“…Pomegranate ( Punica granatum L.) belongs to the genus Punica of the Lythraceae family, and is an essentially valuable fruit tree in the world [ 1 3 ]. It is native to Central Asia region and grows mainly in tropical and subtropical countries such as India, Iran, China, and the USA [ 4 , 5 ]. The consumption of pomegranates has shown a remarkable increase due to their exceptional economic, nutritional, medicinal and ornamental value.…”
Section: Introductionmentioning
confidence: 99%